THE INFLUENCE OF CREDIBILITY AND ATTRACTIVENESS OF BEAUTY VLOGGER AS A CELEBRITY ENDORSER ON CONSUMER PURCHASE INTENTION - Hikmawati Hikmawati (Manajemen Bisnis, 2019)
This study aims to identify the effect of beauty vlogger’s credibility and attractiveness on purchase intention and find the most influential variable. A quantitative approach using survey (questionnaire) was used. The population in this study was 41.517 viewers of Abel Cantika's vlog titled "Demo dan Review the Body Shop New Hair Care Fuji Green Tea”. 100 samples were selected using purposive sampling technique. The results of this study found that both credibility and attractiveness of the endorser significantly influenced purchase intention, the later was found to be the most influential variable.